2007
DOI: 10.4049/jimmunol.178.1.446
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Regulation of IL-1β and Secreted IL-1 Receptor Antagonist Production by Phosphatidylinositide-3 Kinases in Human Monocytes Activated by Lipopolysaccharides or Contact with T Cells

Abstract: The unbalanced production of IL-1β and its natural, specific inhibitor, the secreted IL-1R antagonist (sIL-1Ra), plays an important role in chronic/sterile inflammation. Relevant to this condition is direct cellular contact with stimulated T cells which is a potent inducer of cytokine production in human monocytes/macrophages. We previously demonstrated that activation of PI3Ks is a prerequisite of the transcription of the sIL-1Ra gene in human monocytes activated by IFN-β. In this study, we addressed the ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
2

Year Published

2009
2009
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 60 publications
8
60
2
Order By: Relevance
“…Monocytes (2 ϫ 10 6 cells/well/3 mL) were cultured in 6-well plates with the indicated stimulus for 3 h or 18 h. Total RNA was isolated and analyzed by quantitative real-time PCR as previously described (23).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Monocytes (2 ϫ 10 6 cells/well/3 mL) were cultured in 6-well plates with the indicated stimulus for 3 h or 18 h. Total RNA was isolated and analyzed by quantitative real-time PCR as previously described (23).…”
Section: Methodsmentioning
confidence: 99%
“…HUT-78 cells (2 ϫ 10 6 cells/mL) were stimulated for 6 h by phytohemagglutinin (1 g/mL) and PMA (5 ng/mL). Plasma membranes of stimulated HUT-78 cells were prepared as previously described and solubilized in 8 mM CHAPS (23,44). CHAPS extract of membranes of stimulated HUT-78 cells was referred as to CE sHUT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works demonstrated that CE sHUT and LPS induce IL-1β and sIL-1Ra production in human monocytes [23,24]. Since the levels of cytokine production varied between different monocyte preparations (i.e., blood donors), the results below are presented as percentages of the cytokine production measured in the absence of inhibitor.…”
Section: Production Of Il-1β and Sil-1ra In Human Monocytesmentioning
confidence: 99%
“…In parallel, LPS was used as a prototypical infectious stimulus. Using these models, we previously demonstrated that phosphatidylinositide-3 kinase δ (PI3Kδ) regulate IL-1β and sIL1Ra expression in opposite ways in human monocytes activated by LPS or contact with T cells, dampening the production of pro-inflammarory cytokines in LPS-activated monocytes, but inducing it in contact-activated monocytes [23,24]. Therefore, inhibition of PI3Ks could exacerbate inflammatory response to pathogens.…”
Section: Introductionmentioning
confidence: 99%